GAMBARAN PERAN IBU DALAM PENCEGAHAN HIPERTENSI DI DESA TAWANGSARI WILAYAHKERJA PUSKESMAS PENGASIH II KULON PROGO TAHUN 2017 - Eka Nur Mufidah; Harmilah Harmilah; Agus Sarwo Prayogi (Poltekkes Kemenkes Yogyakarta, 2017)
Hypertension is the silent disease because people doesn't know whether herself infected by hypertension before they checking up her tension. Prevalension hypertension in kulonprogo regency relatively high. the prevention of hypertension extremely needed, especially with the modern life style of people which is more and more practice make risk of hypertension increased. the role of a mother are extremely needed in a prevention of hypertension in a family. The aim of this research are to know how the role of a mother in a prevention of hypertension in Tawangsari village, Pengasih, Kulon Progo in 2017. This research is a descriptive research using survey as the research design. Population as the research subject are 72 people using consecutive sampling method and 47 people as the sample. Closed quizioner as the research instrument. The analysis data using univariat analysis then categorize it using percentage formula. The role of a mother as the manager of a family include the enough category with the percentages 38%, as the educator include in less category with the percentages 45%, as the caretaker include in a good category with the percentages 81%, and as the petron inculed good category too with the percentages 67%. The role of a mother in the prevention of hypertension in Tawangsari village, Pengasih, Kulon Progo include in a good category with the percentages 55%.